Participación del Estado Ecuatoriano Bajo el Principio Precautelatorio de Cuidado de la Naturaleza y del Derecho a la Información de los Mineros; Prevenir sobre el Daño del Uso del Mercurio en la Actividad Minera. - Gaona Gaona, María Bélgica (2022)
This thesis work entitled: “ECUADORIAN STATE PARTICIPATION UNDER THE PRECAUTIONARY PRINCIPLE OF NATURE CARE AND THE MINERS' RIGHT TO INFORMATION, TO PREVENT HARM FROM THE USE OF MERCURY IN MINING ACTIVITIES” is aimed to investigate how the use of mercury violates the rights of nature, determine what the causes and effects are as well as provide miners with information on the damage caused to people and nature by mercury. Moreover, inform all the people who live near the mining areas about the toxicity of mercury, how this metal can enter both human and animal body; plus, raise awareness of the use of this metal in mining. In addition, inform citizens about the legal consequences that a person may face if they are found using this metal. In order to carry out this investigation, methods and instruments such as surveys and interviews with legal practitioners as well as miners were used. The results obtained led to a proposal focused on public policies encouraging both the State and the ministries in charge to work together, give talks on the consequences of the use of mercury and also sponsor, through the media, campaigns on new ways of processing gold. Additionally, the State along with the Police Department, the Mining Regulation and Control Agency and the local governments (GAD) must carry out strategies to control the commercialization of mercury.